2016 Energy Balances - United Nations (United Nations, 2019)
The 2016 Energy Balances contains energy balances for about 220 countries and territories, showing production, trade, transformation and consumption (by sector) in energy units for all energy products. The publications presents energy data for countries and areas in a format which shows the overall picture of the production, trade, transformation and consumption of energy products utilized in the region, published by the United Nations Statistics Division (UNSD). Such a format is useful in assessing and analysing supply and consumption patterns across both products and countries in detail on an internationally comparable basis.